Eijembaum aud Bajtin: Two readings of "The Greatcoat" by Gogol - Wahnón Bensusan, Sultana (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
The Greatcoat, the famous story by Gogol, has been the object of various lectures. This essay compares the lecture of Eijembaum from his famous article "How The Greatcoat by Gogol was composed" to the lecture insinuated by Bqjtin in his work "Rabelais and Gogol", where only in two instances does he refer concretely to this story. Subsequently, this essay proposes on interpretation of The Greatcoat that develops the suggestions of Bajtin and tries to restore the critical and emancipatory significance -profoundly utopic- that the componential analysìs of Eijembaum had taken away from this story.
Keywords: Boris Eichenbaum; Mikhail Bakhtin; Nikolai Gogol; The Greatcoat